2002
DOI: 10.1088/0960-1317/12/4/307
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influence on etching deep holes with SF6/O2 cryogenic plasma

Abstract: A cryogenic SF6/O2 plasma process has been used to investigate the etching of deep holes in silicon wafers. The influence of crystallographic and aspect ratio dependence of the etch rate on the holes profile have been explored. It was found that wafer temperature, during the etching process, played a crucial role in controlling the anisotropy and deteriorative faceting due to crystal orientation dependent etching. High anisotropy and switching of the process to crystallographic independent etching was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…We also confirmed that the proposed method is valid for Si(111) substrates (supplementary data S1). The crystallographic variation of etch rates is not significant at our experimental conditions, although it is known to affect to the etching profile at temperatures below 170 K [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed that the proposed method is valid for Si(111) substrates (supplementary data S1). The crystallographic variation of etch rates is not significant at our experimental conditions, although it is known to affect to the etching profile at temperatures below 170 K [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…For 500 µm diameter holes it is estimated to be 7 µm min −1 . When the front surface of the wafer has been etched down to 13 µm, 45 min are then required to realize the membranes from the backside [16,17].…”
Section: Design and Fabricationmentioning
confidence: 99%
“…It has independent control of radical and ion fluxes and substrate temperature as is described elsewhere [14]. These process setings proved to be adequate for etching holes and open structures [15]. Other process details can be referred to our previous report in [12,13].…”
Section: Design and Fabrication Of The Biomimetic Micromachined Strucmentioning
confidence: 99%